Defective Morphogenesis in MBP1 Null Mutant Strains of Candida albicans is Specific to Solid Media. - Solin, Staci; Humbach, Hannah; Karras, Jenna (My University, 2009)
Candida albicansis a pathogenic yeast capable of undergoing morphogenesis, which is the transition from yeast to hyphalmorphologies. We have previously cloned and partially characterized the MBP1gene of C. albicansand shown that null mutant strains that cannot synthesize the Mbp1 protein are defective in morphogenesis under nitrogen limiting conditions on solid media. To further characterize the function of the Mbp1 gene, the ability of wild-type and MBP1null mutant strains to undergo morphogenesis was assessed when grown in liquid media under conditions that should stimulate morphogenesis.
Color poster with text, table, and images (Spring 2009)
Keywords: Candida albicans; MBP1 gene; Fungi--Genetic aspects; Morphogenesis; Posters